2015
DOI: 10.4094/chnr.2015.21.2.176
|View full text |Cite
|
Sign up to set email alerts
|

School Nurses’ Management for Children and Adolescents with Diabetes

Abstract: The study purposes were to explore school nurses' experience, perceived barriers, and education needs in diabetes management at school. Methods: This study was a cross sectional study and the study participants were recruited conveniently at continuing education seminars for school nurses at Incheon Metropolitan City. Results: Data for 101 school nurses were analyzed. The nurses were all women and their mean age was 46.9 ± 9.3 years. About 66% of them had experience with children with diabetes at school. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…The findings reinforce the appropriateness and importance of a T1DM-specific evidencebased standardized approach of care in CE programs [6][7][8][9]15,17,[22][23][24][25][26]. In previous studies, educational workshops for school nurses were developed based on key components and evidence-based T1DM management [7,9,16,22].…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…The findings reinforce the appropriateness and importance of a T1DM-specific evidencebased standardized approach of care in CE programs [6][7][8][9]15,17,[22][23][24][25][26]. In previous studies, educational workshops for school nurses were developed based on key components and evidence-based T1DM management [7,9,16,22].…”
Section: Discussionsupporting
confidence: 65%
“…These are described in Table 1 . Through an analysis by consensus of 17 studies, the following competencies were identified: strengthening competence in managing students with T1DM [ 6 , 7 , 8 , 9 , 15 , 16 , 17 , 22 , 23 , 24 , 25 ], facilitating networking with experts and peers [ 6 , 7 , 17 ], the perspective of the school nurse as a leader [ 15 , 17 , 22 , 23 , 24 , 25 , 26 ], the use of a T1DM-specific evidence-based standardized approach of care [ 7 , 8 , 9 , 15 , 17 , 22 , 23 , 24 , 25 , 26 ], supporting self-management to promote healthy learners [ 8 , 15 , 17 ], and communication and collaboration between key stakeholders [ 6 , 7 , 9 , 15 , 22 , 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirdly, proper diabetes-care system at school has not yet been established in Korea. One-third of Korean health teachers had no any experiences for managing students with diabetes [25].…”
Section: Discussionmentioning
confidence: 99%